2014
DOI: 10.1353/csd.2014.0055
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Women College Students’ Perspectives on College, Work, and Family

Abstract: Native American and First Nations (hereafter referred to as indigenous*) women college students are faced with a challenge to balance both their culture and the demands of the dominant Western culture in family, school, and work/employment roles. The presence of indigenous women in higher education and in the work force has increased since World War II. While there is an abundance of literature on work-family balance and work-family conflict, with some focus on the perspectives and expectations of college-aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The importance of family and connection to community were noted as crucial to the success of Indigenous students (Kippen et al 2006;Usher et al, 2005;West et al 2013;Day et al 2009;Bingham et al 2014). Most authors also confirmed the importance of cultural, financial & academic support students gained from IESU's.…”
Section: Representation Of Othermentioning
confidence: 75%
See 4 more Smart Citations
“…The importance of family and connection to community were noted as crucial to the success of Indigenous students (Kippen et al 2006;Usher et al, 2005;West et al 2013;Day et al 2009;Bingham et al 2014). Most authors also confirmed the importance of cultural, financial & academic support students gained from IESU's.…”
Section: Representation Of Othermentioning
confidence: 75%
“…A qualitative research design was used in 11 of the 16 research papers (Adams et al, 2005;Plater, 2013;Oloo, 2007;Usher, Lindsay, Miller & Miller, 2005;Kippen, Ward & Warren, 2006;Digregorio, Farrington & Page, 2000;West, Usher, Foster & Stewart, 2014;Bingham, Bearchief Adolpho, Jackson, Alexitch, 2014;Day & Nolde, 2009;Hall, Rata & Adds, 2013;Craven & Dillon 2013), four were mixed methods (West, Usher, Buetther, Foster & Stewart, 2013;Asmar et al, 2011;Oliver et al, 2013;Bennett et al, 2002), and a quantitative research method was used in one study (Pechenkina, Kowal & Paradies, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations